2017
DOI: 10.1016/j.brachy.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

ACR appropriateness criteria: Permanent source brachytherapy for prostate cancer

Abstract: Updated appropriateness criteria for patient evaluation, selection, treatment, and postimplant dosimetry are given. These criteria are intended to be advisory only with the final responsibility for patient care residing with the treating clinicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 87 publications
1
13
0
Order By: Relevance
“…The American College of Radiology Appropriateness Criteria for HDR brachytherapy does not list any recommended dosimetric constraints . This lies in opposition to LDR brachytherapy, where ACR Appropriateness criteria have a recommendation of a urethral V150 < 5% and rectal V100 < 1cc . Most studies looking at correlations are from series where HDR was used in combination with external beam radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The American College of Radiology Appropriateness Criteria for HDR brachytherapy does not list any recommended dosimetric constraints . This lies in opposition to LDR brachytherapy, where ACR Appropriateness criteria have a recommendation of a urethral V150 < 5% and rectal V100 < 1cc . Most studies looking at correlations are from series where HDR was used in combination with external beam radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…17 This lies in opposition to LDR brachytherapy, where ACR Appropriateness criteria have a recommendation of a urethral V150 < 5% and rectal V100 < 1cc. 18 Most studies looking at correlations are from series where HDR was used in combination with external beam radiation therapy. Akimoto et al 19 , for example, found that the urethral dose was the greatest determinant of acute urinary toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…8,23 Implementation of new treatment techniques is now possible due to MRI treatment planning. 8,23 Implementation of new treatment techniques is now possible due to MRI treatment planning.…”
Section: Resultsmentioning
confidence: 99%
“…The application of MRI in brachytherapy treatment planning has become more routine in treatment planning of pelvic malignancies, both in the realm of gynecologic 29 and genitourinary tumors. 8,23 Implementation of new treatment techniques is now possible due to MRI treatment planning. 30 which included 2350 cases of prostate focal therapy, revealed excellent short-and medium-term tumor control and incontinence and erectile dysfunction rates.…”
Section: Resultsmentioning
confidence: 99%
“…Low‐dose‐rate prostate brachytherapy (LDR‐PB) using 125 I‐seed implants is a standard therapeutic approach for low‐risk localised prostate cancer and selected intermediate‐risk patients . Combined therapy, in the form of an LDR‐PB boost to external beam radiotherapy (EBRT) with or without androgen‐deprivation therapy (ADT), has been recommended as an option for the treatment of patients with prostate cancer with a high risk of disease relapse . These recommendations, based on large cohort series, are now supported by Level 1 Evidence from the Androgen Suppression Combined with Elective Nodal and Dose Escalated Radiation Therapy (ASCENDE‐RT) randomised controlled trial .…”
Section: Introductionmentioning
confidence: 99%